Between Inclusion and Fairness: Social Justice Perspective to Participation in Adult Education. (May 2017) - Boyadjieva, Pepka; Ilieva-Trichkova, Petya
The article claims that equity is an indispensable dimension of the widening of access to adult education. Building on the understanding of social justice in adult education as a complex phenomenon, two indicators are developed: an index of inclusion and an index of fairness in participation in adult education. The article analyses social justice separately in formal and nonformal education for two social groups—people with low and high education. Using data from the Adult Education Survey from 2007 and 2011 for 25 countries, it is shown that in most of the countries, there are signs of improvement in the fairness aspect of social justice as a result of a decrease in the overrepresentation of people with high education and in the underrepresentation of people with low education. However, the inclusion of people with low education in adult education remains considerable lower in comparison with the inclusion of people with high education.